Agrobacterium Mediated Transformation Of Sorghum Bicolor For Disease Resistance - INDRA ARULSELVI. P; P.MICHAEL; S. UMAMAHESWARI; S. KRISHNAVENI (International Journal of Pharma and Bio Sciences, 2010)
Sorghum serves as staple food for millions of people in Asia. It ranks as the sixth most planted crop and it is vulnerable to fungal diseases resulting in decreased grain quality and yield loss. Agrobacterium strains used were LBA4404 harbouring pcambia-ubi-chi11 (rice chitinase), EHA105 harbouring pcambia-ubi RC7 (rice chitinase) with bar gene and EHA105 harbouring pMKURF2 (rice chitinase gene) having hph gene for producing fungal resistance in sorghum plants. pCRC7 harbouring chitinase gene driven by ubiquitin promoter was found to be more efficient than pCG11 and pMKURF2.Out of the concentrations of acetosyringone tested, 200µM showed maximum transformation efficiency. Out of the two selection agents tested, bialaphos was found as a suitable selection agent. The transgenic nature of the sorghum calli and plants were shown by transient gus expression, their ability to survive in the selection medium and by western blot. The transformation frequency was found to be very low.